Jak pisać współczesne baśni. Przykład Doroty Masłowskiej "Jak zostałam wiedźmą" - Chłosta-Zielonka, Joanna (Acta Neophilologica, 2022)
The aim of this article is to answer the question as to how to make a child reader interested in and focusing attention on reading. According to Jerzy Cieślikowski and many other researchers, children’s literature has its own rules, poetics of genres, and specific communications circuit: publishing houses, the market, the press, and criticism. Dorota Masłowska employed the form of a literary fairy tale to reach out to a young audience. Using the conventions of this genre, she described one of the most painful problems of modern times – excessive consumerism, in which modern man completely loses himself.